2014
DOI: 10.2355/isijinternational.54.916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screen Open Area on Active Screen Plasma Nitriding of Austenitic Stainless Steel

Abstract: Austenitic stainless steel SUS 316L was nitrided by active screen plasma nitriding (ASPN) using screens with various open areas to investigate the effect of the screen's open area ratio on the nitriding response. The sample was placed on the sample stage in a floating potential and isolated from the cathodic screen and anode. The screen, which was SUS 316L expanded metal mesh with 38%, 48%, or 63% open area ratio, was mounted on the cathodic stage around the sample stage. Nitriding was performed in a nitrogen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 45 publications
0
10
0
4
Order By: Relevance
“…surface layers formed on the surface of the ASPA(N&Ag) samples are dense, almost featureless and uniform in thickness. According to the literatures [18][19][20][21], the formation of these thin surface layerscould be explained according to the principles of active-screen plasma treatment: materials are sputtered from the active screen and then deposit onto the surface during the treatment.The thickness of the top surface layers matches well with the high silver region measured by GDOES ( Figure 5(b)), indicating that the surface deposition layer is rich in silver.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…surface layers formed on the surface of the ASPA(N&Ag) samples are dense, almost featureless and uniform in thickness. According to the literatures [18][19][20][21], the formation of these thin surface layerscould be explained according to the principles of active-screen plasma treatment: materials are sputtered from the active screen and then deposit onto the surface during the treatment.The thickness of the top surface layers matches well with the high silver region measured by GDOES ( Figure 5(b)), indicating that the surface deposition layer is rich in silver.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several researchers have proposed a model of sputtering and deposition during ASPN. 10,13,19,20,35) In this model, nitrogen ions sputter the screen, the sputtered materials form nitrides with nitrogen in the plasma, and nitrides deposit on the sample s surface. It is thought that this model can be adapted to the bias-off of the ASPN process in this study.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] In a previous study, S phase was formed by ASPN. 9,16,17,33,35) A recent research suggested that a deposited layer was formed on the sample surface during ASPN. [36][37][38] However, little information has been reported on the effect of the surface deposits on the nitriding layer formation during ASPN process.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma nitriding is a surface technology to dope nitrogen atoms into metal surfaces via plasma chemical reactions to improve wear resistance, and fatigue strength, etc., of materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Plasma nitriding is now one of the essential surface treatments used in industry, especially in the automobile industry and die/mold fabrication.…”
Section: Research Backgroundmentioning
confidence: 99%